Perspectives on usability and adoption of a new ACL injury prevention programme for female handball players: a mixed methods approach - Tron Krosshaug; Anne Inger Mørtvedt; Erich J Petushek (BMJ Open Sport & Exercise Medicine)
Effective injury prevention programmes (IPPs) hold promise for mitigating ACL injuries in female handball players, yet adherence remains a challenge. This mixed methods study explores the relationship between programme usability characteristics and the potential effectiveness of a newly developed ACL IPP through survey and interview data from 23 female handball players aged 15–18 and their four coaches. Players’ knee abduction moment (KAM) was measured during a cutting task and used to measure potential effectiveness. Findings reveal significant correlations between reductions in KAM and players’ perceived effectiveness of the programme in reducing ACL injury risk and their intention to use it (Spearman’s rho (rs) −0.52, 95% CI −0.78 to –0.1, p=0.02 and rs −0.46, 95% CI −0.75 to –0.03, p=0.04, respectively). Coaches and players identified efficiency and perceived effectiveness as key factors influencing programme adoption. Concerns regarding programme length and doubts about exercise efficacy and transferability emerged as barriers, while perceived effectiveness, efficiency and enjoyability were facilitators for programme use. Players’ suggestions for programme improvement included shortening the duration and incorporating playful elements. Design thinking sessions yielded strategies to optimise time efficiency and integrate IPPs into existing training routines. The study reaffirms the importance of balancing programme effectiveness with practicality and clear communication about its purpose and benefits to facilitate programme adoption. Enhancing programme usability and involving all end-users in the design process are crucial steps toward promoting the acceptance and adoption of IPPs among target populations.